Neuroimaging in the Diagnosis of Chronic Traumatic Encephalopathy: A Systematic Review. (March 2020) - Sparks, Philip; Lawrence, Tim; Hinze, Stephan
Abstract : Objective: Chronic traumatic encephalopathy (CTE) is a neurodegenerative tauopathy associated with repeated subconcussive and concussive head injury. Clinical features include cognitive, behavioral, mood, and motor impairments. Definitive diagnosis is only possible at postmortem. Here, the utility of neuroimaging in the diagnosis of CTE is evaluated by systematically reviewing recent evidence for changes in neuroimaging biomarkers in suspected cases of CTE compared with controls. Data Sources: Providing an update on a previous systematic review of articles published until December 2014, we searched for articles published between December 2014 and July 2016. We searched PubMed for studies assessing neuroimaging changes in symptomatic suspected cases of CTE with a history of repeated subconcussive or concussive head injury or participation in contact sports involving direct impact to the head. Exclusion criteria were case studies, review articles, and articles focusing on repetitive head trauma from military service, head banging, epilepsy, physical abuse, or animal models. Main Results: Seven articles met the review criteria, almost all of which studied professional athletes. The range of modalities were categorized into structural magnetic resonance imaging (MRI), diffusion MRI, and radionuclide studies. Biomarkers which differed significantly between suspected CTE and controls were Evans index ( P = 0.05), cavum septum pellucidum (CSP) rate ( P < 0.0006), length ( P < 0.03) and ratio of CSP length to septum length ( P < 0.03), regional differences in axial diffusivity ( P < 0.05) and free/intracellular water fractions ( P < 0.005), single-photon emission computed tomography perfusion abnormalities ( P < 0.01), positron emission tomography (PET) signals from tau-binding, glucose-binding, and GABA receptor–binding radionuclides ( P < 0.0001, P < 0.005, and P < 0.005, respectively). Important limitations include low specificity in identification of suspected cases of CTE across studies, the need for postmortem validation, and a lack of generalizability to nonprofessional athletes. Conclusions: The most promising biomarker is tau-binding radionuclide PET signal because it is most specific to the underlying neuropathology and differentiated CTE from both controls and patients with Alzheimer disease ( P < 0.0001). Multimodal imaging will improve specificity further. Future research should minimize variability in identification of suspected cases of CTE using published clinical criteria.